The Optimum Phase Ratio of Indonesian Triple Jump Athletes as an Index Detector for Triple Jump Performance - Yadi Sunaryadi; Suherman Slamet (Universitas Pendidikan Indonesia, 2024)
Distribution of triple jump phases was deemed as a technical factor because the phase ratio significantly affects the actual distance in the triple jump. The objective of this study was to identify the phase ratio that is a measure of effort distribution in the triple jump. Hop-dominant, balanced, and jump-dominant techniques were three triple jump techniques defined based on phase ratio which are compared with its of world triple jumpers. The descriptive method was used in this research and subjects were male Indonesian triple jump athletes whose films were taken to be analyzed using Dartfish motion analysis. The percentage analysis obtained from each phase was calculated by comparing it with the total distance of the jump. The largest percentage value of the three phases was the type of jump performed. The performance of the world's triple jumpers was used as a comparative model for analysis to assess the quality of the movement and each athlete's movement sequence form was compared with movement of world triple jumper. The data revealed that the ratio of hop, step, and jump phases was 32% :30% :38%. The phase ratio of Indonesian triple jumper that produced the greatest jump distance was achieved in the jump phase. Despite phase ratio of each subject was wildly different but it was a good index detector of perfect distribution phase that demonstrates the good practice model especially for Indonesia triple jumper athletes.